The Voice Kids Brasil : uma reflexão sobre a infância contemporânea na televisão - Dias, Patrícia Ruas (2018)
This research aims to understand the characteristics of childhood in the contemporary world based on the analysis of the talent show The Voice Kids Brazil, as well as its participants. In this way, it was necessary to reflect on the cultural industry in what concerns celebrities, to understand the operation of the program through theories of cinema and literature, appropriation of concepts about childhood and its history, as well as investigation with the participants of the competition. For the development of the study the methodology used was literary analysis and interview. The interviews conducted served to prove the theories defended by the theorists used in the research.